Innovative Design and Experimental Research of the Patient Transfer Apparatus for MRI Room - Sang, Lingfeng; Liu, Shichuang; Wang, Hongbo; Wang, Zhengcai; Tian, Yu; Vladareanu, Luige (Recent Patents on Mechanical Engineering, 2024)
Background: Patient Transfer Apparatus (PTA), which has been reported by various relevant papers and patents, is widely used in the hospital. However, there are few corresponding transfer apparatuses for research and development in the nuclear magnetic resonance imaging (MRI) room because of the influence of a high magnetic field environment. It is desired to require the apparatus for the patient and the medical staff to have weak magnetism, high matching, and easy operation, etc. Objective: The purpose of this study is to find out the working principle of PTA, to conduct parameter optimization and design and develop more effective PTA for the application of the MRI room. Methods: Firstly, based on the patient transfer process, a novel transfer model with the coordinated movement of the transfer belt and the moving panel is proposed, the corresponding clutch mechanism is conceived and the working principle of the whole mechanism movement is designed and analyzed in detail. Secondly, the force analysis of the clutch mechanism, lifting mechanism and patient transfer mechanism are performed, the mechanical structures are optimized, and the optimal sizes are obtained. Thirdly, the mechanical structure of the system is designed in detail, and the prototype is manufactured. Results: Finally, the performance evaluation of the system is conducted by means of the fuzzy evaluation method and clinical study. The results showed that the motion function of the apparatus is reasonable and it can work normally in the MRI room, the comfort of the PTA is also excellent. The research results also prove the accuracy of the working principle and the rationality of the structural design. Conclusion: The non-magnetic PTA is suitable for quickly transferring patients who are unable to move in the MRI room of a hospital by the manual method.
Keywords: Patient transfer apparatus